Wiki at War : Conflict in a Socially Networked World. - Carafano, James Jay (Texas A & M University Press, 2011)
In 2011, amid the popular uprising against Egyptian president Hosni Mubarak, the government sought in vain to shut down the Internet-based social networks of its people. WikiLeaks editor-in-chief Julian Assange has been branded "public enemy number one" by some in the United States for posting material on the World Wide Web that concerns airstrikes in Iraq, US diplomatic communications, and other sensitive matters. In Wiki at War, James Jay Carafano explains why these and other Internet-born initiatives matter and how they are likely to affect the future face of w.